2019
DOI: 10.1038/s41467-019-13513-7
|View full text |Cite
|
Sign up to set email alerts
|

Saline aqueous fluid circulation in mantle wedge inferred from olivine wetting properties

Abstract: Recently, high electrical conductors have been detected beneath some fore-arcs and are believed to store voluminous slab-derived fluids. This implies that the for-arc mantle wedge is permeable for aqueous fluids. Here, we precisely determine the dihedral (wetting) angle in an olivine–NaCl–H2O system at fore-arc mantle conditions to assess the effect of salinity of subduction-zone fluids on the fluid connectivity. We find that NaCl significantly decreases the dihedral angle to below 60° in all investigated cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 78 publications
2
31
1
Order By: Relevance
“…However, they noted that for the quartz-fluid system, the dihedral angle is drastically reduced upon addition of NaCl, to values as low as 40°. In a more recent study, Huang et al (2019) also observed a reduction of the dihedral angles in the olivine-fluid system to values <60° upon addition of NaCl. In the light of these data, one may plausibly assume that in most crustal lithologies, a HCl and/or NaCl-bearing fluid will likely form an interconnected network and, therefore, strongly enhance bulk conductivity.…”
Section: Remote Sensing Of Magmatic-hydrothermal Systemsmentioning
confidence: 79%
“…However, they noted that for the quartz-fluid system, the dihedral angle is drastically reduced upon addition of NaCl, to values as low as 40°. In a more recent study, Huang et al (2019) also observed a reduction of the dihedral angles in the olivine-fluid system to values <60° upon addition of NaCl. In the light of these data, one may plausibly assume that in most crustal lithologies, a HCl and/or NaCl-bearing fluid will likely form an interconnected network and, therefore, strongly enhance bulk conductivity.…”
Section: Remote Sensing Of Magmatic-hydrothermal Systemsmentioning
confidence: 79%
“…They are in contrast to magmatic podiform chromitites, of which silicate matrix is mainly composed of olivine. The fluid possibly redistributes chromium and chromite (or chromian spinel) within the mantle wedge significantly, where saline aqueous fluids are possibly circulating [67]. It can mobilize Pt and Pd in the mantle wedge and crust significantly, although we need more data and information on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorine and other anions may form complexes with chromium that are soluble in water-rich fluids [21,62,63]. Saline fluids are also expected to be released from the slab to the mantle wedge [64][65][66][67]. If we carefully look peridotite xenoliths derived from the mantle wedge, we frequently observe some textures suggesting accumulation of fine chromite or chromian spinel grains (Figure 14).…”
Section: Origin Of the Fluidmentioning
confidence: 99%
“…In hot subduction zones, such as Cascadia and Mexico, fluids liberated from the shallow subducting slabs at depths of 30-60 km can penetrate through the highly serpentinized mantle wedge and accumulate in the deep fore-arc region (Nakatani & Nakamura, 2016;Reynard et al, 2011). In intermediate and cold subduction zones, in contrast, saline fluid liberated at a depth of ∼80 km can penetrate all the way through the fore-arc mantle wedge without mantle melting and serpentinization due to low dihedral angles (Huang et al, 2019). Therefore, our experimental results can be applied to MT data of intermediate and cold subduction zones where the slab-derived saline fluids can be present in the non-serpentinized fore-arc mantle.…”
Section: Implication: Estimation Of Fluid Fractions In Fore-arc Mantle Wedgesmentioning
confidence: 99%
“…Recently, a growing number of MT observations have revealed high electrical conductivity anomalies (0.001-1 S/m) in the deep fore-arc crust and mantle wedge in some subduction zones (e.g., Araya Vargas et al, 2019;Pommier & Evans, 2017;Worzewski et al, 2011). Because the temperature is relatively low in fore-arc regions (<700-800°C, Syracuse et al, 2010), aqueous fluid rather than silicate melt has been assumed to be the highly conductive phase present in the lower crust and mantle wedge, supplied by the subducting slab through a permeable window in the fore-arc mantle wedge (Huang et al, 2019). Although conductive minerals such as sulfide (Ducea & Park, 2000), graphite (Frost et al, 1989;Glover, 1996), and magnetite (Manthilake et al, 2016) have also been suggested to be the cause of the observed high electrical conductivity, their volume fraction may not be sufficiently high to form interconnected networks in rocks.…”
mentioning
confidence: 99%